ON THE PHYLOGENY AND EVOLUTIONARY HISTORY OF PTEROSAURS - Unwin D.M. (My University, 2003)
Previous cladistic studies of pterosaur relationships suffer from restricted numbers of taxa and characters, incomplete data sets and absence of information on characters, tree structure and the robustness of trees. Parsimony analysis of a new character data set (60 characters, 20 terminal taxa, 93.75% complete) yielded six trees. In the strict consensus tree Preondactylus is the most basal taxon followed, stepwise, by the Dimorphodontidae and the Anurognathidae. Beyond this basal group, more derived pterosaurs (Campylognathoididae (Rhamphorhynchidae + Pterodactyloidea)) share a suite of characters principally associated with elongation of the rostrum. The Pterodactyloidea consists of four major clades. The Ornithocheiroidea is the most basal taxon consisting, stepwise, of Istiodactylus, the Ornithocheiridae, Nyctosaurus and the Pteranodontidae. The remaining taxa, Ctenochasmatoidea, Dsungaripteroidea and Azhdarchoidea, are weakly united in a clade of non-ornithocheiroid pterodactyloids, but their inter-relationships are difficult to resolve. Cycnorhamphus is the basal-most ctenochasmatoid, while the remaining taxa (Pterodactylus, Lonchodectidae, Ctenochasmatidae) form an unresolved trichotomy. The Dsungaripteroidea (Germanodactylus + Dsungaripteridae) is strongly supported by features of the skull and dentition. The Azhdarchoidea (Tapejara [Tupuxuara + Azhdarchidae]) is united by cranial characters such as elevation of the antorbital region, and relative shortening of the wing finger. The pattern of pterosaur evolution suggested by the results of this analysis is broadly similar to traditional ideas, but has greater resolution, more complexity and reveals several previously unrecognized 'events'.